During the wound healing process in penetrating stab wounds of the chest with the damage of the heart - Novoselov, V. P.; Savchenko, S. V.; Chikinev, Yu. V.; Nadeev, A. P.; Ageeva, T. A.; Gritsinger, V. A.; Starostin, S. A. (Patologii͡a︡ krovoobrashchenii͡a︡ i kardiokhirurgii͡a, 2015)
The article presents data on the pathological changes of the myocardium and the development of cellular reaction occurring in stab wounds of the heart, developing in different areas of the wound channel, at various time intervals from the time of injury. The study was conducted using light microscopy and polarization.